(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Elementary school students in low grades are classified as early childhood with strong sensitivity during their development. This period expects parents to optimize guidance and provide appropriate direction for children’s learning activities. Based on mathematics importance in life, the subject’s skills need to be developed from an early stage through proper guidance. Since the Covid-19 pandemic, all learning activities are carried out from home, therefore parents have a bigger role in guiding the children. Parental guidance implementation is important for maximum learning achievement and success. Therefore, this research’s objectives were to (1) provide an overview of mathematics learning guidance implementation in the low grades during the pandemic, and (2) knowing parents’ needs, constraints and obstacles in carrying out the learning process. The method used was descriptive analysis with quantitative and qualitative approaches. The data were obtained through questionnaires, documentation and interviews. Also, the results showed that parental guidance in mathematics learning during the pandemic had not been implemented properly. Parents also experienced various obstacles in guiding the children.